2023
DOI: 10.3390/jcm12030793
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal Laser Ablation of the Prostate (TPLA) for Lower Urinary Tract Symptoms Due to Benign Prostatic Obstruction

Abstract: We aimed to review the current evidence on surgical and functional outcomes of Transperineal Laser Ablation for LUTS due to BPH. A comprehensive review of the English-language literature was performed using the MEDLINE and Web of Science databases until 1 August 2022, aiming to select studies evaluating TPLA for the treatment of LUTS due to BPH. Additional records were found from Google Scholar. Data were extracted and summarized in Tables. An appropriate form was used for qualitative data synthesis. Seven stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(148 reference statements)
1
9
0
Order By: Relevance
“…Sessa et al. [ 3 , 4 ] also used it for large prostates, while de Rienzo et al. [ 6 ] considered it useful for prostates mainly developed in the longitudinal direction and Manenti et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sessa et al. [ 3 , 4 ] also used it for large prostates, while de Rienzo et al. [ 6 ] considered it useful for prostates mainly developed in the longitudinal direction and Manenti et al.…”
Section: Discussionmentioning
confidence: 99%
“…Experts agreed that patients can be discharged 2–4 h after the procedure, despite most studies reported a hospitalization of 1–2 days [ [5] , [6] , [7] , 9 ]. Instead, there are two recent clinical trials in which patients have been safely discharged the same day of the treatment, if no complications occurred during the 2–3 h observation period [ 1 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 One of the most recent additions is the TPLA, with accumulating evidence showing that this is an effective and safe technique. 23,24 Two recent systematic reviews of the literature demonstrated the improvement in functional outcomes with simultaneous low complication rates and preservation of sexual function in the majority of patients; 23,24 yet, the literature search was confined to a period ending in August 2022, since when a number of new clinical studies have been released. In our updated systematic, we included new evidence, including the first reported RCT on TPLA comparing it with TURP.…”
Section: Discussionmentioning
confidence: 99%
“…In January 2023, Sessa et al (26) have published a review with the aim to revise the current evidence on surgical and functional outcomes related to TPLA for LUTS due to BPH. The review included 7 studies of which 6 we have presented.…”
Section: Novel Perspective Among Surgical Approachesmentioning
confidence: 99%